Craqueamento termocatalítico do óleo de buriti (Mauritia flexuosa L.), óleo de palma (Elaeis guineensis) e sabões do óleo de buriti (Mauritia flexuosa L) - SILVA, Marcilene Silva da (Universidade Federal do Pará, 2014)
The present work aims to investigate the Thermocatalytic Cracking Process of the Buriti Oil ( L.), Palm Oil (Elaeis guineensis) and burit oil soap, considering the transformation of vegetable oils and soaps using the thermocatalytic cracking in biofuels, using Na2CO3 (Sodium Carbonate), CaCO3 (Calcium Carbonate), CaO (Calcium Oxide) and Acidic Zeolites (HZSM-5) as catalysts and temperatures of 420, 450 and 480 ° C. The fruit of Buriti (Mauritia flexuosa L) was collected and extracted from the pulp oil, and then this oil was characterized in relation to the Acidity Index, Saponification Number, Viscosity, Density, Refractive Index and CHN analysis. In preliminary tests it was used the refined and neutralized palm oil, so they were not characterized. Buriti soap was prepared in the laboratory with potassium hydroxide and sodium hydroxide and stored for thermal pyrolysis. The catalysts were also characterized in relation to Infrared, Nuclear Magnetic Resonance of 29Si and 27Al, XRay Diffraction, thermal analysis, chemical analysis and TPD of ammonia. In the process of thermocatalytic cracking the liquid products produced were analyzed regarding the parameters: yield, acidity index, infrared spectrum, NMR and CHN analysis and then were characterized in relation to density and kinematic viscosity. However, regarding the level of acidity of the liquid products, only basic catalysts produced cracked with acceptable values for use as fuel. From the results it was verified the efficiency of catalysts in which the sodium carbonate catalyst gave products with low acidity and good characteristics for use as fuel.